1991
DOI: 10.1111/j.1476-5381.1991.tb12205.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lorcainide on microsomal Na+, K+‐ATPase in guinea‐pig isolated heart preparations

Abstract: The effects of lorcainide on the myocardial Mg2+‐dependent, Na+ and K+‐activated adenosine triphosphatase (Na+, K+‐ATPase) were compared in guinea‐pig heart preparations with those of ouabain, a specific inhibitor of the enzyme activity. Both ouabain and lorcainide inhibited the microsomal Na+, K+‐ATPase activity in a concentration‐dependent fashion. Their inhibitory effective ranges were 0.05–100 μm and 0.15–125 μm respectively, and the concentrations for half maximal inhibition (IC50 values) were 2.1 ± 0.3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Lorcainide, like most antiarrhythmic agents in current use, shares this proarrhythmic property (Podrid et al, 1987;Levine et al, 1989). In a recent study (Almotrefi & Dzimiri, 1991a), we have shown that lorcainide is a potent inhibitor of the adenosine 5'-triphosphate (ATP)-hydrolytic action of myo-cardial Na'-K+-ATPase. The implication of this finding with regard to the drug's mode of action is not completely clear.…”
Section: Introductionmentioning
confidence: 99%
“…Lorcainide, like most antiarrhythmic agents in current use, shares this proarrhythmic property (Podrid et al, 1987;Levine et al, 1989). In a recent study (Almotrefi & Dzimiri, 1991a), we have shown that lorcainide is a potent inhibitor of the adenosine 5'-triphosphate (ATP)-hydrolytic action of myo-cardial Na'-K+-ATPase. The implication of this finding with regard to the drug's mode of action is not completely clear.…”
Section: Introductionmentioning
confidence: 99%